Kawah Tekurep: Representasi Kebhinnekaan Kesultanan Palembang Kajian Etnografi terhadap Ragam Hias Nisan di Komplek Makam Kawah Tekurep - Amilda Amilda; Sri Suriana (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2021)
Tekurep Crater is one of the tomb complexes of the Palembang Sultanate which was founded by Sultan Mahmud Badaruddin Jayo Wikramo in 1724 AD. The tombstones found in the Tekurep Crater mausoleum complex have decorations that show how Islam developed in Palembang and the cultural influences that developed on the people of Palembang in the era of the Palembang sultanate at that time. The development of the Palembang sultanate cannot be separated from the influence of the Majapahit and Demak kingdoms in Java, as well as the presence of Hindu and Buddhist influences. The Palembang Sultanate was also influenced by Chinese culture long before the Palembang Sultanate was established, as well as the role of middle eastern scholars who spread Islam in the Palambang region, through close ties to the Aceh Sultanate. Based on the decorations found on the tombstones in the Tekurep Crater complex, this paper will identify the influence of these cultures on the decoration on the gravestones in the Tekurep Crater area. To answer these problems, archaeological research methods are used, namely by describing the existing ornaments and identifying the diversity contained in the tombstones. The identification results were analyzed using culture identity theory to obtain an interpretation of the findings. The results showed that the ornamentation on the tombstones in the Tekurap Crater complex showed influences from Hinduism and Buddhism, Majapahit and Demak influences, Chinese and Acehnese elements, and Islamic </align justify>